1974
DOI: 10.1177/001440297404000401
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Small Group and Tutorial Instruction in Resource Rooms

Abstract: A series of studies compared small group and tutorial instruction in resource room settings. Each child was fought both by a cross-age tutor individually and by a resource teacher in a small group. Results suggested that children learned more from a tutor than in a small group. The effect was observed for word recognition, spelling, oral reading, and multiplication. Tutorial instruction was also superior to self instruction, and tutors appeared to benefit academically from the experience. The results are seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…First, these procedures have become increasingly easy to implement, and they permit the efficient application of the teacher's and peer tutor's skills in the process of individualizing instruction and managing students' dassroom behavior (e.g., Greenwood, Carta, & Kamps, 1990;Greenwood, Delquadri, & Hall, 1989;Grieger, Kauffman, & Grieger, 1976;Kazdin & Geesey, 1977). Second, these procedures are more effective than some conventional teacher-mediated instructional methods (e.g., Greenwood et al, 1990;Greenwood, Dinwiddie et al, 1984;Jenkins, Mayhall, Peschka, & Jenkins, 1974). Third, compared to teacher-mediated forms ofinstruction, these procedures increase the opportunities for appropriate social interactions among peers.…”
mentioning
confidence: 99%
“…First, these procedures have become increasingly easy to implement, and they permit the efficient application of the teacher's and peer tutor's skills in the process of individualizing instruction and managing students' dassroom behavior (e.g., Greenwood, Carta, & Kamps, 1990;Greenwood, Delquadri, & Hall, 1989;Grieger, Kauffman, & Grieger, 1976;Kazdin & Geesey, 1977). Second, these procedures are more effective than some conventional teacher-mediated instructional methods (e.g., Greenwood et al, 1990;Greenwood, Dinwiddie et al, 1984;Jenkins, Mayhall, Peschka, & Jenkins, 1974). Third, compared to teacher-mediated forms ofinstruction, these procedures increase the opportunities for appropriate social interactions among peers.…”
mentioning
confidence: 99%
“…For example, Harris et al (1975) employed a homebased reinforcement program and a response cost procedure to increase weekly assignment completion. Recent investigations have also demonstrated that token reinforcement procedures can be monitored effectively by the peers of underachieving children , and that the peers of underachieving children can effectively tutor children at a number of educational levels (Davis, 1972;Jenkins, Mayhall, Reschka, & Jenkins, 1974;Niedermeyer & Ellis, 1971;Richardson & Havlick, 1975;Shaver & Nuhn, 1971). Until recently most tutorial studies have been evaluated in terms of verbal reports from teachers and students rather than in terms of objective data documenting increased academic performance.…”
mentioning
confidence: 99%
“…Accordingly, one-to-one instruction is considered beneficial for struggling students, especially those who are at-risk for reading difficulties (Bloom, 1984;Jenkins, Mayhall, Peschka, & Jenkins, 1974;Juel, 1991;Wasik & Slavin, 1993) enabling extensive practice that is accustomed to the needs and capacities of each student. However, studies evaluating the efficacy of such environment, stress the importance of constructed program that is carried by trained certified teachers that have the required pedagogical knowledge and background in the field of reading acquisition (e.g.…”
Section: Individualized Literacy Instructionmentioning
confidence: 99%